2014
DOI: 10.3133/sir20145049
|View full text |Cite
|
Sign up to set email alerts
|

Comparability among four invertebrate sampling methods, Fountain Creek Basin, Colorado, 2010-2012

Abstract: Vertical coordinate information is referenced to the North American Vertical Datum of 1988 (NAVD 88). Horizontal coordinate information is referenced to the North American Datum of 1983 (NAD 83). Elevation, as used in this report, refers to distance above the vertical datum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For instance, some of the macroinvertebrate communities in wadeable streams were sampled with the following codes: BERW, IRTH, SWAMP, EMAP, CDPHE, and PNAMP. All methods use kick net samplers with similar mesh sizes, and studies suggest that methods are similar in their ability to detect the presence and absence of taxa [28][29][30] . Fish are collected through seining, snorkelling, backpack or raft electrofishing, or some combination.…”
Section: Comparability Of Sampling Methodsmentioning
confidence: 99%
“…For instance, some of the macroinvertebrate communities in wadeable streams were sampled with the following codes: BERW, IRTH, SWAMP, EMAP, CDPHE, and PNAMP. All methods use kick net samplers with similar mesh sizes, and studies suggest that methods are similar in their ability to detect the presence and absence of taxa [28][29][30] . Fish are collected through seining, snorkelling, backpack or raft electrofishing, or some combination.…”
Section: Comparability Of Sampling Methodsmentioning
confidence: 99%
“…In addition, to account for differences in sampling techniques and equipment, the following method codes for sampling events were selected: BERW, IRTH, SWAMP, EMAP, CDPHE, and PNAMP. Previous studies have suggested that these methods, which use similar mesh sizes, are comparable in their ability to detect the presence and absence of taxa (41)(42)(43). Only area-limited sample data were used.…”
Section: Data Managementmentioning
confidence: 99%